Gender and ethnic disparities in energy poverty: The case of South Africa. (February 2022) - Ngarava, Saul; Zhou, Leocadia; Ningi, Thulani; Chari, Martin M.; Mdiya, Lwandiso
Abstract: The study ascertained the differentiated energy poverty of female-headed households based on their race/ethnicity in South Africa. The study made use of the 2016 General Household Survey (GHS). A sample of 7322 male-headed households and 6170 female-headed households was utilised. An Energy Vulnerability Index (EVI), Independent t -test and Propensity Score Matching (PSM) were used to analyse the data. The results show that male-headed households had more exposure, adaptive capacity and sensitivity to energy poverty compared to female-headed households. Overall, female-headed households were more vulnerable to energy poverty. Compared to White, Indian/Asian and Coloured female-headed households, Black/African female-headed households exhibited more vulnerability to energy poverty. The study concludes that gender of the household head and race/ethnicity of the female-headed households had impact on the energy poverty in South Africa. The study recommends the need to identify relevant gender and race/ethnic issues concerning energy. Furthermore, there is need to counter gendered-ethnic disparities in renewable energy programmes for poorer households, to avail alternative energy sources. Energy policy such as the Free Basic Electricity, besides being pro-poor, should also consider gender and the ethnic divide. Economic opportunities for low income female-headed households should also be promoted to reduce vulnerability to energy poverty. Highlights: Energy insecurity is measurable through the Energy Vulnerability Index. Black/African female-headed households are more vulnerable to energy insecurity. Prioritise gender and race/ethnic divide in energy policy to improve equity.